Knowledge and Attitudes of Pregnant Women towards High-Risk Pregnancies - Sholikah, Siti Mar’atus; Nurwulansari, Fitria; Aini, Elfira Nurul (Poltekkes Kemenkes Palu, 2024)
High Risk Pregnancies contribute to maternal and infant mortality rates. Risk factors in pregnancy can be screened through antenatal care which one of services is health education to increase knowledge and attitudes towards high-risk pregnancies. This study aims to analyze the relationship of knowledge and attitudes of pregnant women with high risk pregnancy events. This research used cross sectional method with the sample consisted of 82 pregnant women in the working area of Wonoayu Puskesmas in Sidoarjo Regency, taken using a simple random sampling technique. The independent variables are knowledge and attitudes of pregnant women, the dependent variable is the incidence of high-risk pregnancy. Data collection used questionnaires to measure knowledge and attitudes towards high-risk pregnancies, as well as the KSPR checklist for screening high-risk pregnancies. Data analysis using Spearman’s Rho and Chi-Square test with significance level of 0.05.The results showed that less than a portion (39%) of respondents with less knowledge, more than a portion (61%) of respondents with a positive attitude, less than a portion (47.6%) of respondents with low risk pregnancies, there is a relationship of knowledge with the risk of pregnancy events high (p 0.027) and there is a relationship between the attitude of pregnant women with high risk pregnancy events (p 0,000). With the conclusion that knowledge and attitude are significantly related to the incidence of high risk pregnancy. Health workers need to develop intensive education and empower families regarding high-risk pregnancies.